2014
DOI: 10.1007/s10995-014-1470-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress Predicts Postpartum Weight Retention

Abstract: Postpartum weight retention (PPWR) is a significant contributor to the development of overweight and obesity in women of childbearing age. Stress may be a key mechanism making it more difficult for mothers to lose weight in the year following delivery. The aim of this study was to assess whether specific aspects of parenting stress and life stress influence postpartum weight retention in new mothers. Women in late pregnancy or up to 2 months postpartum (n = 123) were enrolled in the study and followed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 53 publications
1
59
0
1
Order By: Relevance
“…Recently, a systematic review showed that a research investigating the impact of postpartum sleep, stress, depression on weight retention is limited and future longitudinal studies are needed 40 . Whitaker et al 12 found a significant association between stress and weight retention. Phillips et al 13 showed that weight gain during pregnancy, breast feeding (six or less months), body image dissatisfaction in months three and six after delivery were associated with more postpartum weight retention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, a systematic review showed that a research investigating the impact of postpartum sleep, stress, depression on weight retention is limited and future longitudinal studies are needed 40 . Whitaker et al 12 found a significant association between stress and weight retention. Phillips et al 13 showed that weight gain during pregnancy, breast feeding (six or less months), body image dissatisfaction in months three and six after delivery were associated with more postpartum weight retention.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that psychiatric symptoms are common after delivery, a period marked by hormonal changes, as well as changes of a social nature and shifts in family organization, and by a high frequency of postpartum depression 10 . Sleep disorders and depression also seem to be associated with postpartum weight retention 11,12 . It has been demonstrated that early (three and six months) postpartum body image dissatisfaction is related with postpartum weight retention at nine months 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Herring et al (2008) only found this for only for newly-onset postpartum depression and not for antenatal depression. Furthermore, studies investigating predictors for PPWR have found stress and abnormal sleeping patterns to be potential indicators of PPWR (Siega-Riz et al, 2010;Whitaker et al, 2014). Milder stress, a condition that shares many risk factors and symptoms with depression, is often associated with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…General and postpartum stress as causes of obesity: Physical and mental stress have been implicated as potential causes of obesity [156,157]. Job strain and job related stress have also been implicated in the causes of obesity and overweight [158,159].…”
Section: N Lower Basal Metabolic Rate (Bmr) As a Cause Of Obesitymentioning
confidence: 99%
“…Job strain and job related stress have also been implicated in the causes of obesity and overweight [158,159]. Postpartum stress is also implicated as causes of maternal weight retention and obesity [157].…”
Section: N Lower Basal Metabolic Rate (Bmr) As a Cause Of Obesitymentioning
confidence: 99%